Technè/Technology Researching Cinema and Media Technologies, their Development, Use and Impact - van den Oever, Annie (Amsterdam University Press, 2014)
Techne;/Technology offers a penetrating, close look at the origins of the term techne;, which unleashed a revolution in cinema and media studies when it was first introduced and which continues to influence the study of film as the digital revolution rolls along. The contributors investigate the effects of technologies on major film debates and, moreover, how technologies have affected film theory and its key concepts.